Analisis Strategi Pemasaran Produk Tabungan IB Hijrah Haji Muda pada Generasi Milenial di Bank Muamalat Cabang Stabat - Angga Putra Suhadi; Maryam Batubara; Nursantri Yanti (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to find out the marketing strategy of young IB Hijrah Hajj savings for the millennial generation at Bank Muamalat Stabat Branch. The use of data sources in this study is primary and secondary data. The data analysis technique is using SWOT analysis. This analysis places situations and conditions as input factors, then grouped according to their respective contributions described Internal Factors Analysis Summary. Analysis of external factors EFAS. The results showed that the marketing strategy of the IB Hijrah Haji Muda Savings product carried out by Bank Muamalat Stabat Branch was in a very favorable situation for the company because it had opportunities and strengths so that it could take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy (growth oriented strategy).